Clinical course and predictors of total colectomy in ulcerative colitis; a referral center experience from Turkey - Kalkan, İsmail Hakkı and Dağlı, Ülkü and Kekilli, Murat and Öztaş, Erkin and Tunç, Bilge and Ülker, Aysel (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: We aimed to describe the clinical course of Ulcerative colitis (UC) and the factors that predict the need for total colectomy in Turkish patients with severe UC receiving regular follow up. Materials and Methods: We analyzed the demographic and clinical characteristics of 612 patients with UC receiving regular follow up between 1994 and 2010 in a tertiary referral center in Ankara. Results: Men accounted for 58% of patients (M:F ratio, 1.4:1), and the mean age at diagnosis was 37.9 years. Of these, 32% had distal colitis and 8.8% had further extension, and 39 patients (6.4%) had chronic active disease. Steroid dependency and steroid resistance rates were 7.5% and 17.2%, respectively. In multivariate analysis, steroid dependency (p=0.04), steroid resistance (p=0.002), further extension (p<0.001), presence of extensive disease (p=0.006), and chronic active disease (p<0.001) were independent predictors of the need for total colectomy. Patients with chronic active disease had lower total colectomy free survival (p<0.001). Conclusion: The predictors of total colectomy were comparable with those previously reported in the literature. However, we identified further extension in disease localization to predict the need for total colectomy.